Back Cover: Evaluation of the Sorbent Properties of Single‐ and Multiwalled Carbon Nanotubes for Volatile Organic Compounds through Thermal Desorption–Gas Chromatography/Mass Spectrometry (ChemPlusChem 8/2015). Issue 8 (17th July 2015) - Wong, Gwendeline K. S.; Lim, Li Zhen; Lim, Marcus Jun Wen; Ong, Li Lin; Khezri, Bahareh; Pumera, Martin; Webster, Richard D.
Abstract : The cover picture shows the Merlion, which is often associated with traditional Singapore, while the building is the recently constructed Marina Bay Sands Integrated Resort, which is a popular venue for scientific conferences. The molecules superimposed on the figure are three (of many) volatile organic compounds regularly detected in the atmosphere in Singapore, and have been demonstrated to undergo strong and sometimes irreversible binding on carbon nanotubes. Details are given in the Full Paper by Richard D. Webster et al. onpage 1279 .